2017
DOI: 10.20867/tosee.04.11
|View full text |Cite
|
Sign up to set email alerts
|

Overall Contribution of the Foreign Tourist Demand on Croatian Economy

Abstract: Purpose -The purpose of the paper is to estimate of overall impact of foreign tourist demand on the Croatian output, gross value added and employment. Methodology -The direct, indirect and induced effects of the consumption of foreign tourists to the overall Croatian economy are based on input-output model. Open input-output model was used to calculate the direct and indirect effects of the expenditures of foreign tourists, while the closed input-output model was used to analyze induced effects. Findings -Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Until 2020, tourism was the most important sector contributing to the economic growth of Croatian economy. The analysis of the share of total GVA induced by the consumption of foreign tourists in the GVA of the Croatian economy, ranging from 15.2 percent in 2015 to 18.2 percent in 2019, confirms the previously recognized high importance of the tourism sector for the Croatian economy (Šutalo, Ivandić and Marušić 2011;Ivandić and Šutalo 2018;Mikulić, Keček and Žajdela Hrustek 2017). Epidemiological measures and recommendations to prevent the transmission of COVID-19 disease have influenced a whole range of economic activities in 2020, but tourism has been most affected.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Until 2020, tourism was the most important sector contributing to the economic growth of Croatian economy. The analysis of the share of total GVA induced by the consumption of foreign tourists in the GVA of the Croatian economy, ranging from 15.2 percent in 2015 to 18.2 percent in 2019, confirms the previously recognized high importance of the tourism sector for the Croatian economy (Šutalo, Ivandić and Marušić 2011;Ivandić and Šutalo 2018;Mikulić, Keček and Žajdela Hrustek 2017). Epidemiological measures and recommendations to prevent the transmission of COVID-19 disease have influenced a whole range of economic activities in 2020, but tourism has been most affected.…”
Section: Discussionsupporting
confidence: 70%
“…The IO model was used to estimate direct and indirect effects of tourism sector by Jurčić (1998) and Gelo (2016), and the results of both studies found significant effects of tourism in Croatia. While Ivandić and Šutalo (2018) estimates contribution of both, domestic and foreign tourists, Mikulić, Keček and Žajdela Hrustek (2017) were focused on the multiplicative effects of expenditures of foreign tourists and found increasing economic impacts from 13.1% of Croatian GVA in 2010 to 16.2% in 2014.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stimulating tourism also brings many economic benefits to the links of agri-food value chains (Konishi, 2019;Schubert and Schamel, 2020). In some cases, tourism even helped economies to significantly reduce the overall negative economic impact of recession (Mikulic, Decek and Hrustek, 2017). However, tourism is now affected by an enemy that proved to be very challenging to stand up tothe novel coronavirus disease.…”
Section: Resultsmentioning
confidence: 99%
“…Distribution of expenditures by product groups and sectors are based on results of TOMAS survey(Marušić et al 2020). Methodology of distribution of tourists' expenditures to demand for goods and services delivered by individual economic sectors are explained inMikulić, Keček and Žajdela Hrustek (2017).…”
mentioning
confidence: 99%